VALIDITAS PADA PENGEMBANGAN INSTRUMEN PENILAIAN SIKAP KREATIF MENJAGA LINGKUNGAN SEKITAR MODEL SELF-ASSESSMENT PADA SISWA SEKOLAH MENENGAH PERTAMA - Indriyani Voluntiri Azis; Widowati Pusporini; Christina Dewi Ermawati; Agus Triyana; Nur Eka Ratna Dewi (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
Today, it is necessary to raise awareness in preserving environment. Students’ awareness in preserving the surrounding environment should be measured. Hence schools require an instrument for assessing students’ creative attitudes in the context of preserving a valid and proper environment. The instrument for creative attitude to preserve the environment in the form of self-assessment model for high school students has not been developed. This study aims to describe the instrument’s validity test of creative attitude to preserve surrounding environment which has been developed using the 10 steps of the affective instrument development proposed by Djemari Mardapi. The method used in this paper is a quantitative analysis based on the questionnaire using a 4-option Likert scale. The sample were three teachers. For data analysis, the Aiken formula is utilized to evaluate the content validity. The validity is conducted to evaluate the suitability between the indicators and the concept of creative attitude in preserving the environment. The result of the content validity test indicated an Aiken index of 0.896. Then, the result of the readability test applied to 15 respondents indicated that the 86.7% of those respondents were able to understands the items, the 80% of those respondents responded to the aspects of the ease of the items, and hence it can be concluded that the instrument is feasible for further steps. To sum up, the instrument developed in this study is valid and feasible.